HIRMEOS – High Integration of Research Monographs in the European Open Science infrastructure - Bertino, Andrea (Septentrio Conference Series, 2017)
Open Access has matured for journals, but open access uptake in the book market is still delayed, despite the fact that books continue to be the leading publishing format for qualitative social sciences and humanities. HIRMEOS, High Integration of Research Monographs in the European Open Science infrastructure, is a 30-month EU-funded project and tackles the main obstacles of the full integration of important platforms supporting open access monographs and their contents. HIRMEOS will work on innovative services on identification, entities recognition, annotation, and altmetrics, using when possible common standards. These standards are well established in journal publishing, however not common enough yet in book publishing to pave the way for deeper linking of book and journal content or crosslinking of references, entities or usage. HIRMEOS is based upon 5 Open Access book-publishing platforms, OpenEdition Books, OAPEN Library, EKT Open Book Press, Ubiquity Press and Göttingen University Press. During the run of the project these platforms integrate tools for identification, authentication and interoperability (DOI, ORCID, Fundref), for additional information and entity extraction (INRIA (N)ERD), the ability to annotate monographs (Hypothes.is), and gather usage and alternative metric data. HIRMEOS will also enrich the technical capacities of the Directory of Open Access Books (DOAB), a most significant indexing service for open access monographs globally, to receive automated information for ingestion, while it will also develop a structured certification system to document monograph peer-review. The project consortium will develop shared minimum standards for their monograph publications, such that allow the full embedding of technologies and content in the European Science Cloud. Finally, the project will have a catalyst effect in including more disciplines into the Open Science paradigm, widening its boundaries towards the SSH. The poster will give facts and figures about the involved platforms and their catalogues, the types of services to be implemented and the used standards, the expected benefit for the Social Sciences and Humanities players the global benefits for the Open Science environment